2017
DOI: 10.1371/journal.pone.0179379
|View full text |Cite
|
Sign up to set email alerts
|

Differential induction of apoptosis and autophagy by pyrrolizidine alkaloid clivorine in human hepatoma Huh-7.5 cells and its toxic implication

Abstract: Growing evidence suggests that the pyrrolizidine alkaloids (PAs)-induced hepatotoxicity is mediated by multiple cell death/defence modalities. However, the detailed mechanisms are still lacking. In this study, the hepatotoxic effects of four PAs including three retronecine-type ones (senecionine, seneciphylline and monocrotaline) and one otonecine-type (clivorine) on the proliferation of Huh-7.5 cells and the possible mechanisms were investigated. The results showed that all the PAs could inhibit cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Sustained apoptosis causes cell death and ultimately leads to cell dysfunction ( D’arcy, 2019 ). Previous studies have shown that some PAs can induce apoptosis in primary mouse hepatocytes ( Yang et al, 2017b ) or cell lines, including human live L-02 cells ( Ji et al, 2008 ), human hepatoma cells HepG2 ( Ebmeyer et al, 2019 ), and Huh-7 ( Liu et al, 2017 ). In this study, we tested the toxic effects of MCT with different concentrations and time on primary rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Sustained apoptosis causes cell death and ultimately leads to cell dysfunction ( D’arcy, 2019 ). Previous studies have shown that some PAs can induce apoptosis in primary mouse hepatocytes ( Yang et al, 2017b ) or cell lines, including human live L-02 cells ( Ji et al, 2008 ), human hepatoma cells HepG2 ( Ebmeyer et al, 2019 ), and Huh-7 ( Liu et al, 2017 ). In this study, we tested the toxic effects of MCT with different concentrations and time on primary rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Software-based analyses of the regulated genes indicated that, among others, cellular mechanisms such as cell death, apoptosis and necrosis could be impaired [ 27 ]. Other studies have also indicated connections between PA exposure and the induction of apoptosis in the liver for the PAs monocrotaline, clivorine, retrorsine and senecionine [ 28 , 29 , 30 , 31 , 32 ]. Based on these data, we focused on structural differences in the induction of cytotoxicity and especially apoptosis by 22 different PAs.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the initiator caspases 8 and 9 was less pronounced. PA-induced apoptosis seems to be more likely to occur via the intrinsic signaling pathway (caspase 9-mediated) [ 28 , 30 , 32 ]. Waizenegger et al (2018) and Ebmeyer et al (2019) could nevertheless show that the extrinsic signaling pathway (mediated by Fas via caspase 8) may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…PAs are mainly divided into three types: retronecine (RET)‐type, otonecine (OTO)‐type and platyphylline (PLA)‐type (Figure 1A). The former two bear an unsaturated 1, 2‐double bond in their structure and are highly toxic (Li, Kan, Li, & Lin, 2013; Liu et al, 2017). PAs can be metabolized by cytochrome P450 enzymes (CYP450s) to form dehydropyrrolizidine alkaloids (DHPAs).…”
Section: Introductionmentioning
confidence: 99%